Analysis of The Use of Mobile Banking Applications Using The Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) and Perceived Security Models For PT BCA Digital Customers - Timothy Hans Wijaya; Siska Noviaristanti (Journal Research of Social Science, Economics, and Management, 2024)
The current digital era 4.0 encourages various business sectors to carry out digital transformation, one of which is carried out by the banking sector which is starting to utilize smartphone technology in conducting digital-based banking financial transactions using mobile banking applications. This study aims to analyze the factors that influence the use of BLU Mobile Banking, The research model used in this study is the UTAUT-3 model with the expansion of the model by adding perceived security to customers using mobile banking, which examines the extent to which the construction of PE, EE, SI, FC, HM, HB, PV, PI and PS affects the Behavioural Intention and Use Behavior of Mobile Banking BLU. This study used a quantitative approach with purporsive sampling using the slovin formula with a total of 400 respondents. Data was analyzed using Partial Least Square (PLS) and Structural Equation Modeling (SEM) with SmartPLS data processing tools. The results showed that PE, HM, HB, PI, PS had a positive effect on BI. EE ,SI ,FC ,PV does not have a positive effect on BI. FC, HB and BI have a positive influence on UB. The influence on Behavioral Intention is 58%, while the influence on Use Behavior is 60%. This research can be used as a reference for BLU to focus on implementing mobile banking services as the main strategy in carrying out digital transformation.